Coherent transition radiation from femtosecond electron bunches at the accelerator-based THz light source in Thailand - J. Saisut (2018)
© 2018 Elsevier B.V. A THz radiation source based on electron linear accelerator (linac) has been built and commissioned at the Plasma and Beam Physics (PBP) Research Facility, Chiang Mai University (CMU) in Thailand since 2005. The accelerator system consists of a thermionic cathode RF electron gun, a magnetic bunch compressor in a form of an alpha-magnet, an S-band travelling-wave linac structure, beam steering and focusing magnets, beam and radiation diagnostic instruments, control system and other support components. Electron bunches with an average kinetic energy of about 8 MeV, a bunch charge of 100 pC, and a bunch length of 300 fs can be produced from the PBP-CMU electron linac system. Coherent THz radiation generated via transition radiation technique is used as a source of the THz spectroscopy and THz imaging applications. The measured power spectrum indicates that the radiation obtained from short electron bunches covers the frequency range of 0.15–1.80 THz or the wavenumber range of 5–60 cm−1. Experimental results reveal that a peak radiation power as high as 0.2 MW per micropulse and an average radiation power of 2.5 mW can be obtained. Generation and characterization of the coherent THz transition radiation as well as some examples of experiments to achieve electron bunch length and radiation power spectrum are reported and discussed in this paper.